Unpacking Teacher Beliefs in Curriculum Reform: A Critical Reflection from Pre-Delphi Qualitative Data (International Journal of Education and Literature, 2026)
Curriculum reform in Indonesia has repeatedly emphasized flexibility, deep learning, and student-centered instruction. Nevertheless, many reforms have not been translated effectively into classroom practice. Existing studies tend to focus on teacher competence and policy readiness, while the deeper dimension of teacher beliefs remains underexplored. This study aims to unpack how teacher beliefs shape responses to curriculum reform and to identify the belief-related factors that influence the success or failure of curriculum innovation. A qualitative descriptive design was employed using pre-Delphi reflective questionnaires and Focus Group Discussion data involving senior secondary school teachers and educational stakeholders. Data were analyzed thematically to identify recurring patterns of belief, challenge, and adaptation. The findings reveal that teacher beliefs constitute the most decisive factor in curriculum implementation. Three major themes emerged: (1) a persistent gap between curriculum policy and classroom practice, (2) the difficulty of transforming teachers’ mindsets from fixed to growth-oriented perspectives, and (3) the construction of an ideal teacher identity characterized by reflection, adaptability, collaboration, and moral commitment. More importantly, teachers viewed curriculum change not merely as a technical demand, but as a moral and spiritual responsibility. Curriculum reform will remain ineffective unless it addresses teachers’ internal beliefs. Sustainable transformation requires professional development that integrates cognitive, emotional, and spiritual dimensions of teaching.